Personnel audit process - Pająk, Wojciech (Business, Management and Economics Engineering, 2012)
Audit is one of the basic issues in organisation and management. It consists of a number of constituent problems. One of them is the problem of research methodology. On the other hand, internal audit plays an increasingly important role in improvement of the functioning of an organisation . An attempt to apply the concept of internal audit for the purposes of diagnosing human resource management is the subject matter of this paper. Apart from the problems strictly related to the essence of methodology of personnel audit, an attempt was made to determine the problem range determined by this audit.